2003
DOI: 10.1046/j.1365-2044.2003.02964_4.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of total intravenous with balanced anaesthesia for middle ear surgery: effects on postoperative nausea and vomiting, pain and conditions of surgery*

Abstract: SummaryOver a period of one year, a weekly telephone survey identified 161 stable patients with weaning delay (defined as patients ventilated for at least 6 h per day for more than 2 weeks) in intensive care units in the Northern Region of England. Their median age was 69 years (range 21-88 years). Sixty patients (37%) were admitted with medical conditions, 89 (55%) were postoperative patients, whereas 12 (8%) were surgical but required non-operative admission. One hundred and thirty (89%) were weaned and disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…In control grup the inhalation anesthetics used were halothane (Hasani et al, 2009), isoflurane (Boccara et al, 1998& Cheng et al,2008, sevoflurane (Ozkose et al,2001, Hofer et al, 2003, Pieters et al, 2010& Shin et al, 2010 and desflurane (Van Hemelrijck et al,1991&Fassoulaki et al, 2010. Also, the control groups contained opioids: fentanyl, remifentanil , Mukherjee et al, 2003& Shin et al, 2010 and alfentanil (Petersen-Felix et al, 1996& Davis et al, 1997. Intensity of pain scores was considered adequate (>30 mm VAS) in all trials.…”
Section: Resultsmentioning
confidence: 99%
“…In control grup the inhalation anesthetics used were halothane (Hasani et al, 2009), isoflurane (Boccara et al, 1998& Cheng et al,2008, sevoflurane (Ozkose et al,2001, Hofer et al, 2003, Pieters et al, 2010& Shin et al, 2010 and desflurane (Van Hemelrijck et al,1991&Fassoulaki et al, 2010. Also, the control groups contained opioids: fentanyl, remifentanil , Mukherjee et al, 2003& Shin et al, 2010 and alfentanil (Petersen-Felix et al, 1996& Davis et al, 1997. Intensity of pain scores was considered adequate (>30 mm VAS) in all trials.…”
Section: Resultsmentioning
confidence: 99%
“…5 The results of our study do not support earlier results of clinical association between general anaesthetics and post-operative pain. 4,6,[11][12][13] Possible explanations for these deviations are differences in the sample size estimations, in primary Table 1 Characteristics of patients and surgery. outcome measurements and in the study protocols between the investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Rama-Maceiras et al reported that propofol with remifentanil had a lower incidence of PONV and requirement for antiemetic drugs in patients undergoing plastic surgery, compared with fentanyl [7]. Mukherjee et al reported that patients with TIVA using propofol and remifentanil experienced significantly less PONV with a reduced requirement for antiemetics, compared with balanced anaesthesia using propofol, isoflurane, and fentanyl in middle ear surgery, even though the initial pain score was higher in patients with TIVA using propofol and remifentanil [8]. On the contrary, Del Gaudio et al reported no difference of PONV between remifentanil and fentanyl in target-controlled infusion (TCI) of propofol for elective supratentorial craniotomy [9].…”
Section: Introductionmentioning
confidence: 99%